(3cJGH cdGe GddjGdi hGdCjGes - (3YHO Gddg Hf eMeO Hf YHjO Hf SajGf Hf bjS, CHh HcQ, GHf CHj GdOfjG GdbQTj , J (B281 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3Yf YHO Gddg Hf YeQ Yf CHjg Yf GdfHi Udi Gddg Ydjg hSde bGd (B:( (3eG ef jhe hdG djdg EdG hddg ajg UObg jef HgG Ydi ef jTGA ef YHGOg s
(3BNQgG (B:s
(3bGd eMehO Hf GdMSf GdhQGb (B: (3jMH GdaJi Whd GdHbGA hGfg Ydi KbI Cf GdHbGA afGA RjGOJg ai GdLSe fbU MjGJg hdjS Ydi fbU GdMjGI feGA BNQ cJGH GdCjGe hGddjGdi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B21s
(3GdfSNI HgG MhGTs
(3HBNQg bQGAGJ hSeGYGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B118 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B131s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJUha hGdBOGH GdTQYjIs